1979
DOI: 10.1111/j.1348-0421.1979.tb00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Certain Inhibitors of Glycoprotein Synthesis on Cell Fusion Induced by Vesicular Stomatitis Virus

Abstract: The effect of certain metabolic inhibitors on the fusion of BHK-21 cells induced by vesicular stomatitis virus (VSV) was studied. The polykaryocyte formation in infected cells and virus growth were inhibited by 2-deoxy-D-glucose and Vesicular stomatitis virus (VSV) grows rapidly and is highly cytopathic to several lines of mammalian cell culture (17). Recently it has been reported that marked polykaryocyte formation was observed in monolayers of some cell lines infected with VSV and that the virus replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…VSV-induced membrane fusion occurs at a very narrow pH range and can be avoided by different pH or other factors. [18][19][20] It is conceivable that the culture medium used during the transwell experiments allows release of already cellbound but not fused lentiviral particles. Whether this is a unique property of VSV-G pseudotyped viral particles or can also be observed when using other viral protein envelopes remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…VSV-induced membrane fusion occurs at a very narrow pH range and can be avoided by different pH or other factors. [18][19][20] It is conceivable that the culture medium used during the transwell experiments allows release of already cellbound but not fused lentiviral particles. Whether this is a unique property of VSV-G pseudotyped viral particles or can also be observed when using other viral protein envelopes remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the results obtained previously (14,15), cell fusion induced by VSV in BHK-21-KB cells seemed to be related to specific carbohydrate metabolism. During studies on the inhibitory effect on cell fusion of 2-deoxy-n-glucose and n-glucosamine (14), it was found that polykaryocyte formation in VSV-infected BHK-21-KB cells was not induced in MEM without glucose, and the cytopathic effect was detected only by cell rounding or agglutination. From the results presented here, it can be seen that the rate of polykaryocyte formation was markedly reduced in a medium with less than 5.0 mM glucose while there was no reduction in virus production (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The virus titers were determined by plaque assay in BHK-21-KB cells. One to ten plaque-forming units (PFU) of virus per cell were inoculated and virus adsorption was allowed to proceed for 1 hr at 37 C (14) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations